Isolation, characterization and histopathological study of pathogenic bacteria associated with crown rot of papaya (Carica papaya L.) in Peninsular Malaysia - Mohd Din, Bibi Nazihah (2014)
Papaya, Carica papaya L. is a fast-growing, semi-woody tropical herb and is one of the major fruit crops worldwide that is primarily consumed as fresh fruit. The fruits consist mostly of water and carbohydrate, and are low in calories and rich in natural vitamins and minerals. It is an economically important fruit crop grown in Malaysia with an export value of about RM100-120 million per year. In 2006, a dieback disease was detected in the west coast states of peninsular Malaysia, affecting 800 hectares with significant yield losses and resulting in the destruction of 1 million trees. Affected plants initially show greasy and water-soaked lesions on young stems, petiole axis and buds (crown parts). A total of 40 bacterial isolates were isolated from diseased crowns but only one bacterium (KD33) fulfilled Koch‟s Postulate. The bacterium was successfully identified as Chryseobacterium indologenes based on morphological characteristics and biochemical tests as described in the literature. The pathogenicity of the bacterium (C. indologenes) to its host (papaya) was confirmed by Koch‟s postulate through repeated trials in glasshouse experiments. As the disease develops, necrotic lesions spread downward into the internal tissues resulting in shrinking and drying up of seedlings, and leading to dieback and death of trees, while no symptoms were observed in control plants. The Biolog identification system was used to identify the bacterium as C. indologenes/gluem with a similarity (SIM) index value of between 0.5 and 0.74 at 24 hours of incubation. A high infection probability was recorded. Molecular genotypic identification was used to confirm that the pathogenic bacterium was truly C. indologenes with a 100% sequence similarity and no nucleotide difference between the isolate and reference strain (C. indologenes strain LMG 8337; GenBank Accession Number: NR_042507.1). Neighbour-joining phylogenetic tree analysis revealed that the bacterium belonged to the genus Chryseobacterium and this was supported by a high bootstrap value (99%). The disease progress rate on the petiole axis was the highest (rL= 0.58 unit/day), followed by buds (rL= 0.51 unit/day) and young stems (rL= 0.50 unit/day), while the AUDPC was highest for petiole axis (680 unit2), followed by young stems (600 unit2) and buds (580 unit2). The histological study using light and electron microscopy confirmed the localization and distribution of the isolate bacterium in the infected host, thus demonstrating the high pathogenicity of the C. indologenes bacterium towards papaya. This is a first report of C. indologenes as the pathogen of papaya crown rot in Peninsular Malaysia.